Normal hip strength and range of motion values in youth and adult female national football teams: Data from 504 assessments - Heijboer, W. M. P.; Thijs, K. M.; Weir, A.; Serner, A.; Tol, J. L.; Goedhart, E. A.; Groot, F. P. (Physical Therapy in Sport, 2024)
Objectives To determine normal hip adduction- and abduction strength and range of motion (ROM) values for youth and adult female national team football players, and evaluate if increasing age, playing position and leg dominance were associated with these strength and ROM values.